Career Planning for Malay Culture Students through the Student Career Planning Application (APKAS) - Sulusyawati, Heni; Sonita, Anisya; Sari, Widya Kartika; Hidayati, Arifah; Fitriani, Rahma; Febrianti, Selvi (Corolla International Conference, 2026)
Technological developments certainly have an impact on student career planning, based on the results of observations and interviews, it is still found that students have not prepared their career planning thoroughly; so far students’ career planning has been using a manual system. With the Student Career Planning Application (APKAS), after being tested for validity and feasibility by experts in the field, it can be declared worthy of application. The purpose of this study is to describe the career planning of Malay culture students through APKAS. This study uses a quantitative method with a descriptive approach. The population of this study was grade XII students of SMA Negeri 9 Kota Bengkulu. Sampling used proportional random sampling, with the Slovin formula. The results of this study indicate that the career planning of Malay culture students through APKAS is in the high category. This is indicated by the results of the percentage of the total sample of 160 students, 90 students with a percentage of 56.3% are in the high category, and based on the Malay cultural ethnicity with a sample of 75 students, there are 35 students with a percentage of 47.00% are in the high category. This means that Malay culture students have mature career planning.